Design of a High-Speed PMSM for Flywheel Systems - Boztas, Gullu; Aydogmus, Omur (Ieee, 2019)
The purpose of the current study is to obtain a motor capable of operating at high speeds up to 30,000 rpm for flywheel systems used in mechanical energy storage applications. For this purpose, a Permanent Magnet Synchronous Motor (PMSM) was designed using FEA based MAGNET program. Stator inner radius, slot depth, slot opening width, tooth tip thickness, tooth width, stack, magnet inset depth, magnet thickness, magnet angle, and number of winding turn of the motor were optimized in order to increase the motor average torque and reduce the torque ripple. The average torque was obtained as 0.5488 Nm with 19% torque ripple as a result of the design procedure. It was also analyzed in terms of the motor efficiency, flux distributions, and torque-speed curve. An inset-radial type PMSM which can be used in high-speed applications was designed as a result of the current study.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: PMSM; Motor Design; Flywheel systems